The pragmatics of payment: adventures in first-person economy with Bill Maurer. Issue 3 (3rd May 2016) - Tooker, Lauren; Maurer, Bill
ABSTRACT: Bill Maurer, Dean of the School of Social Sciences, Professor of Anthropology and Law, and Director of the Institute for Money, Technology and Financial Inclusion, all at the University of California, Irvine, has recently joined the Journal of Cultural Economy editorial team. Here, we reproduce an interview with him by Lauren Tooker from September 2014.